2012
DOI: 10.1002/hec.2814
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality and Mental Health—empirical Evidence From Australia

Abstract: The causal association between absolute income and health is well-established; however, the relationship between income inequality and health is not. The conclusions from the received studies vary across the region or country studied and/or the methodology employed. Using the Household, Income and Labour Dynamics in Australia panel survey, this paper investigates the relationship between mental health and inequality in Australia. A variety of income inequality indices are calculated to test both the income ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 50 publications
(56 reference statements)
0
28
0
1
Order By: Relevance
“…Eight articles reported results from multi-country studies 12,27,29,[31][32][33][34][35] ; ten studies were conducted in the USA 28,30,[36][37][38][39][40][41][42][43] ; three studies were carried out in the UK [44][45][46] ; two articles reported results from a study carried out in Brazil 47,48 ; one study was conducted in Australia 49 , one in Mexico 50 , one in Spain 51 , and one in South Africa 26 (Table 1).…”
Section: Figure 1 About Herementioning
confidence: 99%
See 4 more Smart Citations
“…Eight articles reported results from multi-country studies 12,27,29,[31][32][33][34][35] ; ten studies were conducted in the USA 28,30,[36][37][38][39][40][41][42][43] ; three studies were carried out in the UK [44][45][46] ; two articles reported results from a study carried out in Brazil 47,48 ; one study was conducted in Australia 49 , one in Mexico 50 , one in Spain 51 , and one in South Africa 26 (Table 1).…”
Section: Figure 1 About Herementioning
confidence: 99%
“…One article included university students 35 , one included 11, 13 and 15-year-old students 31 and one sampled women with infant children 40 . Twenty-two articles assessed psychiatric diagnoses 12,[26][27][28][29][30]32,[34][35][36][37][39][40][41][42][43][44][45][46][47] , whereas three assessed psychological distress/symptoms or mental well-being/functioning 31,33,49 . One article assessed both psychiatric diagnosis and psychological symptoms 38 , and one article reported use of mental health services 48 .…”
Section: Table 1 About Herementioning
confidence: 99%
See 3 more Smart Citations